MANUSKRIP AL-QUR`AN DI ‘BUMI SENENTANG’: ASPEK KODIKOLOGI PADA MANUSKRIP AL-QUR`AN KOLEKSI KESULTANAN AL-MUKARRAMAH KABUPATEN SINTANG, KALIMANTAN BARAT - Parwanto, Wendi; Riyani, Riyani (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2023)
ABSTRACT This article aims to describe the codicological aspects of the Qur'anic manuscripts, including the historiology, form, illumination, symbols, and others. The study employed library research with primary data on al-Qur`an manuscripts at the Al-Mukarramah Sintang palace. The study found that that this manuscript is the only manuscript of the Al-Qur`an in the Sintang palace, estimated to be 340 years old, written by Sultan Abang Nata and H. Abdul Karim, and its authorship was sponsored by the Al-Mukarramah Sintang palace. The base of the manuscript is tapa bark wood typical of the Dayak community in rural West Kalimantan, indicating the integration of Kalimantan culture with the writings of the Quran at that time. Furthermore, the type of khat used in the manuscript is naskhi using black ink on the Arabic text and red ink on letter descriptions, waqaf and vowel (syakl). Seventh, there is no thick illumination, only the use of simple lines and circle models as markers of waqf and juz markers. Keywords: Codicology, Quran manuscripts, Al-Mukarramah Palace, Sintang ABSTRAK Artikel ini bertujuan untuk menjelaskan aspek kodikologi pada manusÂkrip al-Qur`an, seperti historisitasnya, bentuk, iluminasi, simbol dan lainnya. Jenis penelitian ini adalah studi kepustakaan dengan data primer manuskrip al-Qur`an di istana Al-Mukarramah Sintang. KesimÂpulan artikel ini menjelaskan bahwa: Pertama, manuskrip ini merupakan manuskrip al-Qur`an satu-satunya yang ada di keraton Sintang diperkiraÂkan berumur 340 an tahun, ditulis oleh Sultan Abang Nata dan H. Abdul Karim dan kepenulisannya disponsori oleh istana Al-Mukarramah Sintang. Alas manuskrip adalah jenis kayu tapa kulit kayu khas masyaÂrakat Dayak di pedalaman Kalimantan Barat, mengindikasikan bahwa adanya integrasi budaya Kalimantan dengan penulisan al-Qur`an pada masa itu. Selanjutnya, jenis khat yang digunakan dalam manuskrip adalah naskhi menggunakan tinta berwarna hitam pada teks Arab dan tinta berwarna merah pada keterangan surat, waqaf dan harakat (syakl). KetuÂjuh, tidak ditemukan iluminasi yang kental, hanya berupa penggunaan garis dan model lingkaran sederhana sebagai penanda waqaf dan penanda juz. Kata Kunci: Kodikologi, Manuskrip Al-Quran, Istana Al-Mukarramah, Sintang.